Treatment outcome of patients co-infected with tuberculosis and HIV in Abuja, Nigeria - Jamda, Mustapha; Oladimeji, Olanrewaju; Yassin, Mohammed; Gurgel, Ricardo; Baamlong, Nicholas; Tafida, Ishaku; Okechukwu, Josephine; Abdurrahman, Sadiq; Nafarnda, Wesley; Adelaiye, Rabi; Fredrick, Christy; Umobong, Ema; et al. (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Tuberculosis (TB) has been a major cause of morbidity and mortality in Nigeria and Sub-Saharan Africa. The burden of the disease has increased with the high prevalence of human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) in Nigeria and Africa in general. The resultant effect has worsened the prognosis of tuberculosis treatment. This study aimed to determine the prevalence of TB-HIV co-infection relative to other cities/countries and compare the outcome of TB treatment among HIV-infected and non-infected patients in Abuja, Nigeria. Materials and Methods: Hospital records of TB patients registered for treatment in 39 health facilities in Federal Capital Territory (FCT)-Abuja were reviewed. Treatment records were selected through multi-stage sampling. Treatment outcome of patients-completion of treatment, death, treatment failure, default in treatment or transferred out-with and without HIV co-infection were compared. Results: Two hundred and forty-five (49%) of 501 adult TB patients were co-infected with HIV. Among HIV co-infected patients, 156 (64%) completed treatment, 12 (4.9%) died, 1 (0.4%) failed treatment, 41 (17%) defaulted, 30 (12%) were transferred out and 5 (0.02%) had an unknown outcome. Among the 256 HIV-negative patients, 172 (71%) completed treatment, 3 (1.2%) died, none failed treatment, 36 (15%) defaulted, 24 (10%) were transferred out and 6 (0.02%) had an unknown outcome. Conclusion: Abuja has one of the highest proportions of TB-HIV co-infection rates in Sub-Saharan Africa. The outcome of patients with TB co-infected with HIV was less successful than among HIV-negative patients, with statistically significant higher mortality.